Answer:
y = 2x² + 18x + 36
Step-by-step explanation:
Given
y = 2(x + 6)(x + 3) ← expand the factors using FOIL
y = 2(x² + 9x + 18) ← distribute parenthesis by 2
= 2x² + 18x + 36 ← in standard form
Answer:
x=-6
Step-by-step explanation:
X^2 + 8x - 5 = 0
a = 1, b = 8, c = -5
x = ( - 8 + - sqrt(64 - 4*1*-5))/2
x = ( -8 + - sqrt(64+20))/2
x = ( -8 + - sqrt (84))/2
x = ( - 8 + - 2sqrt21))/2
x = -4 + - sqrt21
Answer:
x - 13 = 13 - x
Step-by-step explanation:
The commutative property of addition is a+b=b+a
The third equation is the only one not following the rule. It states that a-b=b-a, whoich is not true.
For exaple, 2-1 is not equal to 1-2.
The missing side of the fence measures 15 ft
The perimeter of the fence is 40 ft
The area inside the fenced in section is 60 ft²
The fence is triangular and a right triangle.
<h3>Right triangle:</h3>
A right triangle has one of its angle as 90 degrees. Therefore, the sides can be found using Pythagoras theorem.
c² = a² + b²
17² - 8² = b²
b = 15 ft
AC = 15 ft
perimeter of the triangle = 15 + 8 + 17 = 40 ft
Area of the triangle = 1 / 2 × 15 × 8 = 60 ft²
Therefore,
The missing side of the fence measures 15 ft
The perimeter of the fence is 40 ft
The area inside the fenced in section is 60 ft²
learn more on right angle triangle here; brainly.com/question/2192748